Dynamics of Individual Red Blood Cells Under Shear Flow: A Way to Discriminate Deformability Alterations - Atwell, Scott; Badens, Catherine; Charrier, Anne; Helfer, Emmanuèle; Viallat, Annie (Frontiers in Physiology, 2022)
In this work we studied the dynamics of motion in shear flow of individual red blood cells (RBCs) from healthy donors, and from patients with sickle cell disease (SCD) or Sickle Cell-β-thalassemia. At the lowest shear rates, biconcave discocyte-shaped RBCs present a flip-flopping unsteady motion, whose variations with the shear rate depend on RBC density, thus disclosing a difference in the behaviour of young and old cells, regardless of SCD. Upon increasing the shear rate, a transition to steady tank-treading motion is observed, that is significantly shifted towards higher shear rates for old cells and towards even higher shear rates for SCD cells. In the latter case the shift is attributed to the strong increase in RBC cytoplasmic viscosity previously reported in the literature. Finally, both flip-flopping motion and tank-treading transition are highly sensitive to the cell shear modulus, allowing the detection of or Sickle Cell-β-thalassemia RBCs which hardly undergo transition to tank-treading. Our results suggest that it might be possible to develop simple non-invasive assays for diagnosis purpose based on the RBC motion in shear flow and relying on microfluidic techniques.